Effect of Basil Leaves (Ocimum sanctum L.) Infusion as Hepatoprotective Agent Induced by Paracetamol - Ni Nyoman Yuliani; Jefrin Sambara; Maria Hilaria; Harlinda Harlinda (Indonesian Journal of Cancer Chemoprevention, 2016)
Indonesia has  biodiversity potential to be developed as medicinal plants, such as basil leaves (Ocimum sanctum L.). Basil was reported to have a very high antioxidant activity in vitro. The aim of this study was to determine the effect of basil leaves (Ocimum sanctum L.) infusion to liver based Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) value in each dose. 18 rats were divided into 6 groups.,  control group,  negative control group treated with CMC Na 0.5%,  positive control group treated with Curcuma 3.6 mg / 200gBB, groups of 4-6 consecutive given a 80 mg  dose infusion basil / 200 gBB, 160 mg / 200 gBB, 320 mg / 200 gBB for 8 consecutive days, on the day of the 4th and 8th all treatment groups induced by toxic doses of paracetamol (500 mg / 200 gBB) except the normal control group 1, The research data in the form of enzyme activity of AST and ALT were analyzed using parametric and nonparametric ANOVA, and Friedman test with the level of trust  then followed by SNK test and Bnj test. The statistical test result with a 95% of level of trust that shown basil infuse with a dose of 80mg / 200gBB, 160mg / 200gBB, 320mg / 200gBB have hepatoprotective effects in rats induced by paracetamol 500mg / 200gBB. Based on the result of changes in average levels of AST on the fourth day and the eighth day of the three treatment infusion, infusion at a dose of 160 mg / 200gBB most effectively reduce average levels of AST and a group that has the average AST closest to the control group is positive, but infusion at a dose of 320mg / 200gBB the group that has the closest average ALT positive control group.Keywords : hepatoprotective, Ocimum sanctum L, Paracetamol